THE GENDER ROLE CHANGE OF SCARLETT OHARA AS A PORTRAYAL OF THE HIGH-CLASS SOUTHERN WHITE WOMENS LIFE - Angelika Riyandari; Heny Hartono (Soegijapranata Catholic University, 2006)
The high-class Old Southern United States women had played their gender roles as wives, dolls, drudges, playmates, breadwinner and heroines for both their families and country. The coming of the American Civil War in 1861 was one important event for these women to prove themselves as an independent figure in the danger of invasion and famine without help from men. From their beginning gender role as a graceful wealthy plantation mistress then suddenly reduced into poverty, Margaret Mitchell portrays the struggle of these women in the figure of Scarlett OHara as the protagonist character of her only novel.